1933 Wash. Sess. Laws 335-36, ch. 64, §§ 1-5 - (:unkn) unknown (My University, 1933)
Prohibited manufacturing, owning, buying, selling, loaning, furnishing, transporting, or possessing a machine gun.
Keywords: MACHINE GUN RESTRICTION